2003
DOI: 10.1076/icsp.10.1.69.14107
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of road traffic injuries in Ghana: Implications for control

Abstract: Road traffic injuries and fatalities are increasing in Ghana. Police-collected crash and injury data for the period 1994-1998 were aggregated and analyzed using the MAAP5 accident analysis package developed by the Transport Research Laboratory, U.K. Published results of recent transport-related epidemiological and other surveys provided an additional data source. According to the 1994-1998 police data, road traffic crashes were a leading cause of death and injuries in Ghana. The other leading causes of death a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
105
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(115 citation statements)
references
References 4 publications
10
105
0
Order By: Relevance
“…This means that males have a higher tendency of not complying with traffic laws than females in Ghana. This corroborates findings from various studies such as Vlahogianni (2013); Vardaki and Yannis (2013);Farah, (2011);Romano et al (2012);Nordfjaern et al (2012;2010); Iversen and Rundmo (2004); Afukaar et al (2003); Yagil (1998);Odero et al (1997) and Harre et al (1996).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…This means that males have a higher tendency of not complying with traffic laws than females in Ghana. This corroborates findings from various studies such as Vlahogianni (2013); Vardaki and Yannis (2013);Farah, (2011);Romano et al (2012);Nordfjaern et al (2012;2010); Iversen and Rundmo (2004); Afukaar et al (2003); Yagil (1998);Odero et al (1997) and Harre et al (1996).…”
Section: Discussionsupporting
confidence: 81%
“…In line with the findings of other studies by Vlahogianni and Golias (2012);Farah (2011);Forward (2010);Yan et al (2007); Kontogiannis et al (2002);Parker et al (1995), Yagil (1998), Deery (1999), Afukaar et al (2003); Iversen and Rundmo (2004), results of the study revealed that drivers' age has significant effect on the frequency of commission of traffic violations. From the study, younger drivers report a more often violation of traffic laws than old drivers.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In low-income and middle-income countries, other types of motor vehicle are more often involved. In Ghana, 37.8% of pedestrian traffic deaths involve cars, but the cars are often taxis; 31.8% buses or minibuses; 18.6% heavy trucks; 7.6% light trucks; 2.1% motorcycles; 0.8% bicycles; and 1.3% other (105).…”
Section: Risk Of Injury From Poor Vehicle Design and Maintenancementioning
confidence: 99%